2014
DOI: 10.2478/v10241-012-0011-9
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Well-Being and Self-Regulation of Emotions in Daily Executive Dysfunctions and Psychological Distress

Abstract: An emerging literature has begun to document the emotional consequences of everyday executive functions on emotional distress. Little is known, however, about whether this relation is mediated by other variables.A multiple mediation model was proposed to integrate core concepts of daily executive dysfunctions with emotional distress in order to increase understanding of their relationship to psychological well-being and emotional regulation. The working hypothesis was that dimensions of well-being and emotiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Studies with basic emotions support the idea that EF, in particular inhibition, plays a key role in the use of ER strategies. For instance, Domingo and Armentia found that cognitive reappraisal significantly mediated the association between executive dysfunctions and psychological distress in students [ 103 ]. In agreement, Fatima and Shahid found that cognitive reappraisal, but not suppression, mediated the relationship between EF, especially inhibition, and Machiavellianism [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies with basic emotions support the idea that EF, in particular inhibition, plays a key role in the use of ER strategies. For instance, Domingo and Armentia found that cognitive reappraisal significantly mediated the association between executive dysfunctions and psychological distress in students [ 103 ]. In agreement, Fatima and Shahid found that cognitive reappraisal, but not suppression, mediated the relationship between EF, especially inhibition, and Machiavellianism [ 104 ].…”
Section: Discussionmentioning
confidence: 99%